2020
DOI: 10.3390/plants9121770
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Hormone Dynamics and the Expression Profiles of SUT/SUC and SWEET Sugar Transporters during Flower Development in Petunia axillaris

Abstract: Flowering is the first committed step of plant sexual reproduction. While the developing flower is a strong sink requiring large quantity of sugars from photosynthetic source tissues, this process is under-temper-spatially controlled via hormone signaling pathway and nutrient availability. Sugar transporters SUT/SUC and SWEET mediate sugars movement across membranes and play a significant role in various physiological processes, including reproductive organ development. In Petunia axillaris, a model ornamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…Most SWEET genes of watermelon showed high expression levels in male flowers [ 73 ]. During the petunia flower development, the expression level of PaSWEET13c , - 9a , - 1d , - 5a and - 14a increases with the maturation of the flower [ 74 ]. During the anthesis, JsSWEET1 , - 2 , - 5 , - 9 , - 10 , - 16 and - 17 were highly expressed in the flowers of Jasmine ( Jasminum sambac ) [ 75 ].…”
Section: Sweets Are Involved In Plant Growth and Developmentmentioning
confidence: 99%
“…Most SWEET genes of watermelon showed high expression levels in male flowers [ 73 ]. During the petunia flower development, the expression level of PaSWEET13c , - 9a , - 1d , - 5a and - 14a increases with the maturation of the flower [ 74 ]. During the anthesis, JsSWEET1 , - 2 , - 5 , - 9 , - 10 , - 16 and - 17 were highly expressed in the flowers of Jasmine ( Jasminum sambac ) [ 75 ].…”
Section: Sweets Are Involved In Plant Growth and Developmentmentioning
confidence: 99%
“…The involvement of sucrose transporters in phytohormone signaling and abiotic responses was already described in other species-for example, SlSUT2 and StSUT4 proteins were found to interact with brassinosteroid signaling, ethylene sensing, gibberellic acid responses, and auxin transport in tomato and potato (Bitterlich et al, 2014;Garg et al, 2022a). PaSUT and OsSUT1 were found to interact with hormone (auxin and cytokinin) signaling pathways to regulate the carbohydrate partitioning in Petunia axillaris flower (Rolland et al, 2002;Iftikhar et al, 2020) and the reproductive organ of rice (Zhao et al, 2022), respectively. Consistent with these conclusions, we found that DfSUT4, DfSUT5, and DfSUT6 showed significant increases in expression in response to ABA treatment within 9 h (Figure 4B).…”
Section: Discussionmentioning
confidence: 66%
“…PtaSUT4 transporters also function in photosynthesis (Frost et al, 2012) and drought response (Harding et al, 2020). Furthermore, PaSUT and OsSUT1 transporters are associated with phytohormone (auxin and cytokinin) signaling pathways in the translocation of sucrose in Petunia axillaris flower (Rolland et al, 2002;Iftikhar et al, 2020) and rice seeds (Zhao et al, 2022), respectively. More importantly, PttSUT3 transporters are responsible for carbon delivery and formation of wood fibers in a hybrid aspen (Mahboubi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SWEET transporters function as Suc exporters, releasing Suc to the apoplast, and their function is essential for phloem loading [89]. Several events of plant development such as the embryonic and reproductive tissue development in A. thaliana, Glycine max, and Petunia axillaris have been related to the carbohydrate transport activity of SWEET proteins [90][91][92].…”
Section: Sucrose Transporters and Sucrose Mobilization In Mycorrhizal...mentioning
confidence: 99%